The Intelligent Use of Forensic Data: An Introduction to the Principles. Issue 1 (7th June 2016) - Bruenisholz, Eva; Prakash, Sameer; Ross, Alastair; Morelato, Marie; O'Malley, Troy; Raymond, Michael Anthony; Ribaux, Olivier; Roux, Claude Patrick; Walsh, Simon
ABSTRACT: For the past decade, the National Institute of Forensic Science (NIFS) has been involved in and committed to raising the awareness of forensic intelligence in Australia. In this context, a discussion paper was written and distributed across Australia and New Zealand covering forensic intelligence principles and offering a 'quick reference' guide. In addition, NIFS jointly facilitated a set of papers on forensic intelligence that was published in the Australian Journal of Forensic Sciences. The implementation of forensic intelligence requires substantial planning and adaptation within an organization. There must be commitment within an agency to refocus outcomes so that crime prevention and disruption become priorities along with the traditional focus on the court. This implies many changes including a shift from a single case focus to a multi-case focus and a breaking down of existing interdisciplinary silos. At a time of budget restrictions, the resources to implement these changes are often difficult to identify. However, established intelligence cells within forensic science facilities are realizing the benefits to be gained from this approach. The primary aim of this paper is to raise awareness on the principles and practice of forensic intelligence through the collation and integration of recently published findings and observations. It is intended to provide introductory principles to personnel of various levels and disciplines involved in law enforcement, including forensic scientists, police officers, and those involved in administering the criminal justice system.